CREDIT BUSINESS STRATEGY OF REGIONAL DEVELOPMENT BANK IN THE FACE OF TECHNOLOGICAL DISRUPTION (CASE STUDY: PT. BANK SULSELBAR) - Muhammad Daefnur Hafsir; Nurdin Brasit; Nuraeni Kadir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
The purpose of this study intends to answer the formulation of the problem is to find out the side of the credit segment affected by P2P lending. The next goal is to identify and evaluate factors included in the internal and external environment in determining credit business development strategies at PT. Bank Sulselbar and determine the use of effective methods be developed at PT. Bank Sulselbar. This research is a type of qualitative research on strategic design. This research is designed to direct managerial strategy decisions at PT Bank Sulselbar based on scientific analysis and argumentation. Based on the results of QSPM matrix analysis, the right strategy that can be carried out for PT Bank Sulselbar is to conduct market development, followed by product development. The results of the study on the formulation of corporate strategies that have been presented in this research, it is expected to help encourage a more in-depth study of the field of strategy management, especially in the field of corporate strategy formulation.